Kulturowa mobilizacja w Ukrainie podczas pełnoskalowej rosyjskiej inwazji (2022) - Olzacka, Elżbieta (Przegląd Wschodnioeuropejski, 2025)
The article aims to explain how Ukrainian culture was utilized as a tool to mobilize both Ukrainian and global society in the early months following Russia’s full-scale invasion of Ukraine. In the first part, the cultural policy of Ukraine during the initial hybrid phase of the Russian aggression against Ukraine. The second part focuses on selected cultural initiatives that were implemented with the aim of mobilizing Ukrainian society. Finally, the article discusses cultural diplomacy during the full-scale Russian invasion, aimed at informing the global public about the war and securing moral and material support for the fight. The article analyzes existing sources, obtained mainly from the official websites of Ukrainian cultural institutions and Ukrainian media.